2013
DOI: 10.1016/j.jcmg.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Dyssynchrony and the Risk of Ventricular Arrhythmias

Abstract: Baseline LV dyssynchrony did not predict VT/VF/death or VT/VF in mild heart failure patients with or without LBBB. CRT-induced improvement of LV dyssynchrony was associated with significant reduction of ventricular arrhythmias in patients with LBBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 41 publications
3
40
1
3
Order By: Relevance
“…Post-TAVR LBBB and pacing-induced dyssynchrony may be reasons for worsened outcomes in this population. 34 Indeed, further investigation including whether or not cardiac resynchronization therapy has a role in this population needs to be pursued. Of equal importance is the need to determine whether or not unnecessary PPI post-TAVR is associated with worsened outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Post-TAVR LBBB and pacing-induced dyssynchrony may be reasons for worsened outcomes in this population. 34 Indeed, further investigation including whether or not cardiac resynchronization therapy has a role in this population needs to be pursued. Of equal importance is the need to determine whether or not unnecessary PPI post-TAVR is associated with worsened outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Penicka et al (11), Fauchier et al (27), and Bader et al (10) reported that LV dyssynchrony was prognostic of cardiac endpoints. Kutyifa et al (28) investigated VT/VF events and LV dyssynchrony in mild heart failure patients with LBBB and an implanted CRT device and compared them to patients with non LBBB and demonstrated that improved synchrony might translate into a reduction of ventricular arrhythmic events in LBBB patients. Ludwig et al (29) reported that patients with heart failure and LBBB, acute RVA pacing induces greater mechanical dyssynchrony and further impairs LV function.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In the presence of abnormal substrate, several studies have showed increased risk of adverse cardiovascular outcomes in patients with dyssynchrony but data on arrhythmic events are less convincing. [8][9][10][11] A sub-study of MADIT-CRT showed no difference in the occurrence of ventricular arrhythmias in patients undergoing CRT implantation with or without baseline dyssynchrony. 10 In REVERSE trial there was no difference in occurrence of ventricular arrhythmias in patients with CRT ON vs CRT OFF implying resynchronization had little impact on occurrence of ventricular arrhythmias.…”
Section: See Related Article Pp 555-569mentioning
confidence: 99%
“…[8][9][10][11] A sub-study of MADIT-CRT showed no difference in the occurrence of ventricular arrhythmias in patients undergoing CRT implantation with or without baseline dyssynchrony. 10 In REVERSE trial there was no difference in occurrence of ventricular arrhythmias in patients with CRT ON vs CRT OFF implying resynchronization had little impact on occurrence of ventricular arrhythmias. The study population in this trial included patients with mild heart failure (NYHA classes I and II) with QRS greater than 120 ms and since there was no baseline assessment of dyssynchrony it is plausible that most of these patients did not have significant dyssynchrony to begin with.…”
Section: See Related Article Pp 555-569mentioning
confidence: 99%